THE SUICIDE IN ITS TO REVEAL IT PROFESSIONAL OF HEALTH - Magali Roseira Boemer; Viviane Picinato da Silva (Universidade Federal de Goias, 2004)
The number of suicide case and attempting are increasing at last decades and became a great concernin many countries. In front to my observations and literature consulting, an important question emerged from: Do theprofessional who care people with attempting suicide history are prepared to deal with this situation? This study wasconduced on a Phenomenological Inquiry method with medicine doctors, nurses and nursing staff professionalsPsychiatric Clinic at the Emergency Unity of the Sao Paulo Ribeirão Preto Clinical Hospital, from July to August2003. The following guiding question was proposed: How suicide shows for you? From interviewing answers analysis,thematic categories was constructed revealing, thus, that the suicide is shown to these professionals as something thatoccurs at a desperation moment, which people appeals to call attention and something that awakes to them a diversityof feelings. From speeches analysis was possible to understand that the study evidences the necessity of introducing,in mental health area, specialized professionals. The specialization makes possible to the professionals to better dealwith the preconceptions and difficulties, thus opening, perspectives for a better care to the people whom do notperceive sense in their own lives.